The involvement of MiR-1-clathrin pathway in the regulation of phagocytosis. - Cuilian Liu (Public Library of Science (PLoS), 2014)
Phagocytosis, one of the most powerful immune responses, is a complicated process regulated by many factors. However the regulation of phagocytosis mediated by microRNAs has not been extensively investigated. To address this issue, the regulation of phagocytosis by miR-1 was characterized in this study. The results showed that miR-1 played an important role in the phagocytosis regulation in shrimp in vivo. The sequence analysis indicated that miR-1 was highly conserved from invertebrates to mammals, suggesting that miR-1 might share the similar or same functions in phagocytosis of shrimp hemocytes and mammalian macrophages. The data presented that miR-1 was significantly downregulated in cancerous macrophage RAW264.7 cells compared with those in the isolated murine macrophage and in the immortalized macrophage ANA-1. The findings showed that miR-1 had a great effect on the regulation of phagocytosis in cancerous macrophage by the inhibition of clathrin heavy chain 1 (CLTC1) gene. Therefore our study presented a novel miR-1-mediated regulation of phagocytosis both in invertebrate and in vertebrate.